Lyophilization and evaluation of the stability of 'Ataulfo' mango pulp (Research, Society and Development, 2021)
In order to develop a product of high durability and that do not have changes in its physical-chemical, nutritional and sensory characteristics, the objective of this work was to study the production of lyophilized powders from the 'Ataulfo' mango in three different maturation stages (2, 3 and 4), as well as its storage in two types of  packaging followed by analysis of their physical and physical-chemical characteristics. The powders were stored in two packages, one laminated and the other made of polyethylene. at room temperature, it lasted 180 days and every 30 days, analyzes were made for water activity (aw), humidity, color (L *, a * and b *), vitamin c, soluble solids (Brix °) and titratable total acidity (ATT). The results were tabulated with the assistance of the Assistat software, and the design used was entirely randomized in a factorial scheme using the test. Tukey's at 5% probability and regression analysis. Based on the results, physical and physical-chemical differences of the 'Ataulfo' mango pulp powders were observed in the three different maturation stages; whereas freeze-drying is an efficient and effective drying process for dehydrating mango pulp; and mainly that the laminated packaging worked throughout the storage period as a barrier promoting the best preservation in general of the physicochemical properties of the powders.